Legal insanity and risk: An international perspective on the justification of indeterminate preventive commitment. (September 2019) - Bijlsma, J.; Kooijmans, T.; de Jong, F.; Meynen, G.
Abstract: Modern legal systems typically link the insanity or diminished responsibility of an offender for a crime committed in the past to his future dangerousness. This nexus serves across legal systems as a justification for the indeterminate commitment of the offender with diminished or no criminal responsibility. Conceptually, however, insanity and risk are not related legal issues. Moreover, empirical research suggests that there is only a weak link between insanity, diminished responsibility and mental illness on the one hand and risk of recidivism on the other. Other risk factors seem to be more important. The inference of risk from insanity or diminished responsibility that lies at the heart of the indeterminate commitment of mentally disordered offenders is therefore problematic. This should lead to a reconsideration of the preconditions for indeterminate commitment of mentally disordered defendants.